A study on the effects of forced air-cooling enhancements on a 150 W solar photovoltaic thermal collector for green cities. (February 2022) - Shrivastava, Anurag; Prakash Arul Jose, J.; Dilip Borole, Yogini; Saravanakumar, R.; Sharifpur, Mohsen; Harasi, Hossein; Abdul Razak, R.K.; Afzal, Asif
Abstract: The major goal of this research is to identify optimal arrangement of forced cooling enhancements such as baffles and fins. This research focuses to determine the effect of the different configurations for achieving higher thermal efficiency of the 150 W solar photovoltaic thermal collectors (PV/T). The air-cooling enhancements evaluated in this PV/T system are free duct without fins, ducts with fully transverse fins, partially transverse fins, longitudinal fins with straight baffles and inclined baffles. The experiments are done on hot days of summer in May 2018, India and achieved diverse flow rates of air mass ranging from 0.012 to 0.016 kg/s. The Reynolds number obtained in the flow experiments are in the range of 900–1300 and Nusselt number 35–130.A Computational fluid dynamics study was established to achieve a parametric research to determine surface and outside profiles to study the cooling effectiveness. The impacts on flow rate of air mass on the outlet T, Reynolds Number, coefficient of heat transfer and Nusselt number were studied. The maximum irreversibility occurred at the free type fins whereas minimum irreversibility obtained at longitudinal type with inclined baffles and detected that PV/T system have a prodigious impact on the energy efficacy as well as energy losses increased with increasing surface T. This research displayed that the coefficient of heat transfer of solar panel upsurges by means of growing Reynolds number. Additionally, the PV module thermal efficacy by growing flow rate and reduced with increasing friction factor. An increase by 6–8% in exergy efficiency and 5% to 7% in energy efficiency was recorded while using these forced air-cooling enhancements. A reasonable agreement was reached between experimental and computational model. The exergy performance was increased from 20% to 28 % while using air cooling duct with longitudinal fins and inclined baffles. The thermal energy performance was increased from 12 to 18 % while using air cooling duct with longitudinal fins and inclined baffles. This is the maximum energy efficiency achieved in this PV/T system with the Nusselt number ranging from 30 to 130 and Reynolds number 900–1300. This study showed that Nusselt number of PV/T system upsurges with growing Reynolds number of air flow. The PV module thermal efficacy upsurges by means of growing flow rate as the friction factor increases. The longitudinal fins with inclined baffles provided higher friction factor, thereby ensured higher heat transfer rate. The fins and baffles employed in our research are economical and relaxed to manufacture and install. They bid a fairly lower friction lack in movement of air and henceforth do not necessitate higher fan power. This set up can be used for green and smart cities as it helped to reduce the energy consumption considerably.